Software development for induction motors - performance and high efficiency motor - Majid, M. S.; Rahman, Hasimah Ab.; Hassan, M. Y.; Seng, L. C.; Ern, N. C. (2006)
This paper presents the software development of induction motor to determine its performance and comparison of standard efficiency motor and high efficiency motor. An interactive tool to obtain the approximate equivalent circuit and performing economic analysis has been developed using Microsoft Visual Basic 6.0. Microsoft Access is used to upload the data for each motor into the software database.